(untitled) (Epidemiology, Biostatistics, and Public Health, 2025)
Introduction Anemia, a chronic condition affecting millions globally, poses greater risks to pregnant mothers, particularly in regions like Yemen. However, data on pregnancy-related anemia in Yemen is scarce. This study aimed to gauge anemia prevalence in Yemen’s Dhamar governorate, identifying associated pregnancy-related risk factors. Methods Through a questionnaire-based cross-sectional study involving a total of 157 pregnant participants, data on sociodemographics (age, education, income) and health history (gestational age, parity, hemorrhage) were collected. Utilizing SPSS v25, frequencies, percentages, and binary logistic regression (OR, AOR) with 95% confidence intervals (p<0.05) were calculated. Discussions Results highlighted 17% of pregnant women in medical centers had anemia (43% of which are mild, 23% moderate, 33% severe). Significantly, rural residence and lower socioeconomic status were linked (p=0.021, 0.015) with AORs of 0.305 (CI: 0.111-0.835) and 3.86 (CI: 1.294-11.542). Conclusion In conclusion, anemia affects pregnant women, particularly those in rural areas with lower incomes. Addressing this requires targeted medical interventions to mitigate anemia’s prevalence and impact during pregnancy.